2021
DOI: 10.3389/fphar.2021.768436
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Mediated Drug Delivery With a Clinical Ultrasound System: In Vitro Evaluation

Abstract: Chemotherapy efficacy is often reduced by insufficient drug uptake in tumor cells. The combination of ultrasound and microbubbles (USMB) has been shown to improve drug delivery and to enhance the efficacy of several drugs in vitro and in vivo, through effects collectively known as sonopermeation. However, clinical translation of USMB therapy is hampered by the large variety of (non-clinical) US set-ups and US parameters that are used in these studies, which are not easily translated to clinical practice. In or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 67 publications
1
15
0
Order By: Relevance
“…In addition to increasing the intercellular permeability of hydrophilic molecules across the epithelial barrier, USMB induced intracellular accumulation of SYTOX TM green (molecular weight 600 Da) and two dextrans (molecular weight 4 and 20 kDa) as was already shown by us [ 26 , 37 ] and other groups [ 38 , 39 , 40 ] before. Quantification of fluorescent signals 30 and 120 min after incubation revealed that intracellular accumulation of dextrans was significantly higher in the cells treated with USMB at 0.7 MPa as compared to 0 MPa.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…In addition to increasing the intercellular permeability of hydrophilic molecules across the epithelial barrier, USMB induced intracellular accumulation of SYTOX TM green (molecular weight 600 Da) and two dextrans (molecular weight 4 and 20 kDa) as was already shown by us [ 26 , 37 ] and other groups [ 38 , 39 , 40 ] before. Quantification of fluorescent signals 30 and 120 min after incubation revealed that intracellular accumulation of dextrans was significantly higher in the cells treated with USMB at 0.7 MPa as compared to 0 MPa.…”
Section: Discussionsupporting
confidence: 71%
“…New studies using molecules with various hydrophilicities and molecular weights could help to comprehend the potential and limitations of USMB therapy in ocular drug delivery. Ideally, clinically approved microbubbles and a clinical ultrasound system could be used for USMB treatment [ 26 ] and to monitor microbubble emissions [ 56 ]. Finally, combination of USMB with pharmaceuticals (such as an anti-CXCR4 nanobody for the treatment of retinoblastoma) could be tested in in vivo disease models in order to determine the therapeutic efficacy of the method.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The improvement of drug/gene delivery by ultrasound in the presence of microbubbles has been widely studied. The combination of ultrasound and contrast agents of different compositions has been successfully applied in vitro and in vitro to molecules that hardly or not cross the cell membrane such as as cisplatin and bleomycin. Evaluation of this approach in phase I clinical trials, although in a limited number of patients with pancreatic and hepatic cancer, has generated interesting results in terms of safety and drug clinical efficiency. , In a recent study using ultrasound in the presence of microbubbles and erythrocytes as carriers, increased trehalose uptake, an effective sugar for protection against desiccation, has been demonstrated by Centner et al with improvement of recovery of viable erythrocytes following freeze-drying and rehydration. The presented study is in the continuity of our previous publications exploiting the strong potential of ultrasound as an alternative tool for drug and nucleic acids delivery. , A moderate correlation was found between inertial cavitation and hemolysis.…”
Section: Discussionmentioning
confidence: 99%